Pengelolaan Sumber Daya Pesisir Secara Seimbang di Provinsi Nusa Tenggara Barat - Vicky Sanofa; Taslim Sjah; Muhammad Sarjan (Lembaga Bale Literasi, 2024)
This study discusses the management of coastal resources in the Province of West Nusa Tenggara (NTB) with a focus on current conditions, integrated management strategies, and policy recommendations. The NTB Provincial Government has issued NTB Governor Regulation Number 100 of 2023 concerning Whale Shark Management in the Saleh Bay Waters to regulate management and tourism activities in the area. However, challenges such as environmental degradation, land use conflicts, and climate change remain major obstacles. This research employs a literature review method with a normative approach and qualitative data analysis. The results indicate that effective coastal resource management requires the integration of local knowledge, community-based management practices, and sustainable management policies. Active community participation and collaboration between the government, communities, and other stakeholders are crucial to achieving harmony between economic utilization and environmental conservation. One of the coastal areas that has become a tourist destination and a coastal management program is in Labuhan Jambu Village, Sumbawa, which focuses on whale shark ecotourism. Awareness of human responsibility towards nature and the integration of science, technology, and local values are also necessary for the sustainable management of coastal resources in NTB.